ANALISIS KRIMINOLOGI KORUPSI ANGGOTA DPRD SUMUT TERKAIT LAPORAN PERTANGGUNGJAWABAN PELAKSANAAN APBD (Studi Kasus Korupsi Anggota DPRD Sumut) - Santoso, Santoso; Marzuki, Marzuki; Purba, Nelvitia (Jurnal Ilmiah METADATA, 2021)
The form of corruption committed by members of the North Sumatra DPRD related to the accountability report of the Provincial Government's APBD in the 2012-2014 Fiscal Year is bribery or gratuity, which is related to the implementation of its functions and duties in making legislation (legislation), approving the budget ( budgeting), and supervision (controling) of the implementation of local government policies. Bribery as a criminal offense for corruption in the PTPK Law is regulated in several articles, namely: Article 5 paragraph (1) letters a and b, Article 11, Article 12 B, Article 13 of the Corruption Eradication Law. Corruption committed by DPRD members from a criminological perspective is a crime. Interpretation of crimes against an act that is categorized as a criminal act of corruption, because the act is deemed to have caused unrest for the community. Efforts to prevent and eradicate corruption, which are ideal in a criminological perspective, can be carried out in two ways, namely penal and non-penal efforts.